2022
DOI: 10.47259/ijrebs.332
|View full text |Cite
|
Sign up to set email alerts
|

Customer Usage Behavior of FinTech Products in Sultanate of Oman

Abstract: Purpose: The objective of this research paper is to analyze the constructs behind the FinTech usage behavior and which factors contribute to the new financial technologies and to what extent demographic profiles affect FinTech adoption in Oman and analyze the factors that contribute to new business models of financial institutions from the adoption of convergent technologies in FinTech. Design/methodology/approach: This paper provides a comprehensive literature review focused on scholarly and practitioner expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…In addition, it was identified that effort expectancy is a significant determinant that affects consumers’ behavioral intention. Rubaia and Pria (2022), Rabaa’i (2021) and Kurniasari et al (2023) validate our findings, but Hassan et al (2023) and Hassan et al (2022) contradict our findings. Moreover, it was uncovered that there is a significant impact of effort expectancy on customer satisfaction, which is supported by past studies of Chao (2019) and Esawe (2022).…”
Section: Findings and Discussionsupporting
confidence: 81%
“…In addition, it was identified that effort expectancy is a significant determinant that affects consumers’ behavioral intention. Rubaia and Pria (2022), Rabaa’i (2021) and Kurniasari et al (2023) validate our findings, but Hassan et al (2023) and Hassan et al (2022) contradict our findings. Moreover, it was uncovered that there is a significant impact of effort expectancy on customer satisfaction, which is supported by past studies of Chao (2019) and Esawe (2022).…”
Section: Findings and Discussionsupporting
confidence: 81%
“…Beberapa penelitian terdahulu yang mendukung hal tersebut di antaranya, penelitian Al Rubaiai and Pria (2022) di Oman menyatakan bahwa adanya hubungan yang positif signifikan antara perilaku manajemen keuangan terhadap fintech payment. Kemudian penelitian oleh Li et al (2022) pada mahasiswa di China menyatakan bahwa fintech berpengaruh positif terhadap perilaku konsumsi seorang individu.…”
Section: Pendahuluanunclassified